Effects of cage and barn rearing system on early laying performance of pullet (Bangladesh Journal of Animal Science, 2016)
The present experiment was conducted with 144 Shaver 579 egg laying pullets to compare their performances reared on barn and in cages for a period of 16 weeks from 25 to 40 weeks of age. Feed consumption, feed conversion (FC) and egg weight were significantly higher when reared on barn than in cages. However, hen day egg production (HDEP), egg mass, body weight, livability, albumen index, Haugh unit (HU), yolk index, shape index and egg shell thickness did not differ (P>0.05) between pullets under two different rearing systems. Soiled eggs (p